2017
DOI: 10.1080/02656736.2017.1365953
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on the clinical and preclinical dosage limits of interstitially administered magnetic fluids for therapeutic hyperthermia based on current practice and efficacy models

Abstract: We offer a critique of what constitutes a suitable dosage limit, in both clinical and preclinical studies, for interstitially administered magnetic nanoparticles in order to enable therapeutic hyperthermia under the action of an externally applied alternating magnetic field. We approach this first from the perspective of the currently approved clinical dosages of magnetic nanoparticles in the fields of MRI contrast enhancement, sentinel node detection, iron replacement therapy and magnetic thermoablation. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 75 publications
0
48
0
Order By: Relevance
“…62 The amount of NP in our formulations (50mg being the biggest quantity) is well below the amounts used in FDA approved iron oxide based formulations such as Feraheme or Resovist that can be used in mice from 0.6 mg to 12.3 mg, respectively. 63 Furthermore, even with this type of NP taking several weeks to be degraded, the administered amount are not capable to become toxic, while reports in the literature indicate that it can be used by the body as nutrient iron or be excreted in the feces after degradation. 64,65 The formulation used here efficiently induced a Tc1 response, which heightens the potential use of this formulation (Tc1 inducer) in cases where the TCD4 response is not efficient, such as in AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…62 The amount of NP in our formulations (50mg being the biggest quantity) is well below the amounts used in FDA approved iron oxide based formulations such as Feraheme or Resovist that can be used in mice from 0.6 mg to 12.3 mg, respectively. 63 Furthermore, even with this type of NP taking several weeks to be degraded, the administered amount are not capable to become toxic, while reports in the literature indicate that it can be used by the body as nutrient iron or be excreted in the feces after degradation. 64,65 The formulation used here efficiently induced a Tc1 response, which heightens the potential use of this formulation (Tc1 inducer) in cases where the TCD4 response is not efficient, such as in AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] IONPs have been used in cancer therapy through magnetic hyperthermia, where the NPs produce heat when exposed to a high‐frequency alternating magnetic field. [ 18 ] Although IONPs have not been explicitly investigated in NP‐enhanced radiotherapy, they have undergone several in vitro studies for hyperthermia applications, where they have demonstrated cellular uptake. [ 19 ] It was therefore of interest to determine if these larger‐sized NPs would demonstrate similar enhancements to the other NPs considered, when combined with radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Currently there are four clinically approved intravenous or interstitial iron-oxide-based magnetic fluids, the dose limits for which are given in Table 2. It should be noted that for the intravenous agents, Resovist® and Feraheme®, the dose limits quoted relate to the manufacturer's published instructions for use; but that for the interstitial agents, Sienna+® and Nanotherm®, the dose limits have been derived from published data, using post-hoc assumed values for the dispersion factors of v = 2.4 ml tissue /ml fluid in both cases [7]. As such, the tabulated intravenous limits are expected to be more robust and reliable than the tabulated interstitial limits.…”
Section: Clinical Dose Limits Of Existing Agentsmentioning
confidence: 99%
“…which equals 144 mg Fe /ml fluid (see Table 3). In this way, the DRF method has been used to predict a maximum permissible dose (that scales with patient mass) for agent #1, and to set Table 2 Published and derived dose limits for clinically-approved intravenous and interstitial magnetic fluids [7]. The method also establishes treatment limits.…”
Section: Application To New Product Developmentmentioning
confidence: 99%
See 1 more Smart Citation